Gift of fear [videorecording (DVD)] - Kohler, Carly; Kohler, Jack; Cortez, Justin Johnson; Vallejo, Laura; Horse, Michael (Random Media, 2024)
Mili watched in horror as her mother was murdered 11 years ago. Now 17, Mili's former gang kidnaps her girlfriend. Tribal cops and the FBI are on the case, but Mili waited for the authorities once she won't wait this time.